RC circuit response - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
RC circuit consists of a resistor and a capacitor which are connected in series. This chapter focuses on how the voltage develops (or shrinks) with a constant voltage source, V, is turned on (or off). Generally speaking, a capacitor accumulates charge for a current flow in, and obviously current flow out of a capacitor results into charge depletion. The current flow into an uncharged capacitor is maximum, equal to VIR at the instant in time when the circuit is closed, alternatively we can say that an uncharged capacitor acts like a short circuit at t=0. However, current flow drops exponentially to reach zero when capacitor gets fully charged to act like an open circuit. Capacitor unlike a resistor from an electrical view point shows more complex current-voltage relation. Also, besides being a charge storage element, capacitor is like a delay element too with a time constant given by r=RC